Cirebon Language Honorific: Communication Ethnography Study on Pembatik Community in West Cirebon - Afifah, Wiwiek (Master Program in Linguistics, Diponegoro University, 2017)
This naturalistic qualitative research attempts to reveal the use of honorific in West Cirebon. The research focus relies on the three aspects: (1) linguistic forms for honorific, (2) influencing factors, and (3) the principles underlie the used of the language. The data sources taken to this research are from men and women whose professions are ‘pembatik’ and who live in Kalitengah kecamatan Tengahtani, West Cirebon of West Java. The research found that (1) the honorific forms for the address terms consist of words and phrases; (2) based on their culture and custom, the adreess terms used by the local society comprises of five areas such as; (a) personal address terms, (b) relative, (c) occupation, (d) title both for academic and non-academic degree, and (e) religious address terms. The factors influencing the use of the terms are social factors such as education degree, age, and economic level and situational, and situational factors which refers to with whom they talk to, what language used in the communication, the setting of the communication, as well as the topic talked by them; 3) the underlied principles are the willingness to make a friendly communication and to show respect.